Identification and functional application of a new malonyltransferase NbMaT1 towards diverse aromatic glycosides from Nicotiana benthamiana. Issue 34 (12th April 2017) - Liu, Yuyu; Wang, Xiaohui; Mo, Ting; Yan, Yaru; Song, Yuelin; Zhao, Yunfang; Li, Jun; Shi, Shepo; Liu, Xiao; Tu, Pengfei
Abstract : A new malonyltransferase NbMaT1 from Nicotiana benthamiana with significant substrate tolerance was identified and used in the chemo-enzymatic synthesis of diverse bioactive malonylated glycosides derivatives in this article. Abstract : Recently, owing to the important pharmaceutical properties of malonylated glycosides, their chemoenzymatic synthesis using malonyltransferase has received significant attention. In the present study, a new malonyltransferase, NbMaT1, was identified from Nicotiana benthamiana . Extensive enzymatic assays revealed its significant substrate tolerance based on HPLC-UV and HR-MS analyses. Moreover, 16 of the tested glycosides including flavone glycosides, flavonol glycosides, dihydroflavone glycosides, isoflavone glycosides, coumarin glycosides, and phenylethyl chromone glycosides with various sugar moieties (such as glucose, xylose, and galactose) substituted at different positions of their skeleton could be accepted by NbMaT1 to conduct the corresponding malonylation. Among these, enzymatic malonylation of phenylethyl chromone glycosides as well as xylosides and galactosides has rarely been reported earlier. Furthermore, one-pot synthesis using the known malonyl-CoA synthetase MatB and NbMaT1 as well as an unnatural fusion protein MatB–NbMaT1 was designed, which allowed malonic acid to be directly used in the malonylation reaction without the addition of expensive malonyl-CoA. Moreover, a remarkably improved conversion rate was observed for all the tested substrates, with both commercial and industrial application values. The malonylated product of the bioactive flavonoid diglycoside icariin was prepared and NMR spectroscopy revealed that the malonyl group was specifically transferred onto the 6-OH group of the glucose moiety. NbMaT1 was expected to be a universal and effective tool for chemoenzymatic synthesis of diverse bioactive-malonylated glycoside derivatives for drug discovery.